Semiosis and Metamorphosis - Rastier, François (2021)
Independently of the generative and enunciative theories, the dynamic structuralism of the Saussurian tradition has made it possible to set out the problem of semiosis, which is understood as the individuation of the sign from a structural germ. At a higher level of complexity, the processes that preside over this individuation seem to also govern the composition of texts. Certain literary and pictorial examples make it possible to detect them, and they confirm that reflection on the arts is a major area of general and comparative semiotics.